The Implementation of Leverage Secondary Association through Stakeholder Approach in Reinforcing Brand Knowledge: The Case Study of Wanderlust, Local Tourism Agent, Indonesia - Iin Mayasari; Fatchiah E. Kertamuda; Handrix Chris Haryanto; Mochammad Rivee Arham (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2019)
There are three main objectives of this study namely 1) analyzing the application of secondary association leverage in strengthening the Wanderlust company brand products, 2) analyzing the implementation of stakeholder approaches in supporting brand strengthening and the sustainability of Wanderlust, and 3) determining the extent to which the application of secondary association leverage, whose main orientation is in strengthening the brand and the sustainability of the company, basically directly or indirectly reinforces the cultural products of one region. This study uses a qualitative approach as a method for data retrieval. Case study research raised in this regard relates to the existence of tour and travel companies under the name of Wanderlust in strengthening the company's brand awareness. The interview approach with the owner of Wanderlust is the most appropriate method in its efforts to explore the processes carried out by Wanderlust in strengthening branding using the Leverage Secondary Association approach. Based on the results of empirical research that has been done it can be concluded that the leverage secondary association in the Wanderlust company has shown strength in the company. This can be seen from the four elements that support it, namely people, places, things, and other brands. These four elements have been optimally carried out by Wanderlust to support the sustainability of his company in order to create equity in his company.